Model Discovery Learning untuk Meningkatkan Kemampuan Kognitif Siswa pada Mata Pelajaran Biologi - Nia Kurniati (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2022)
In the learning planning of cycle I and cycle II after using the discovery learning model, learning increased significantly both from the teacher and student side. Learning is in accordance with the syntax of the discovery learning model and the realm of cognitive abilities of students. The discovery learning model process to improve students' cognitive abilities in biology subjects in class X MIPA 1. Teachers have used the discovery learning model effectively and proportionately taking into account students' cognitive abilities. So that some students in the cognitive ability test results in cycle II increased significantly compared to cycle I and pre-cycle. The success of the discovery learning model to improve students' cognitive abilities in the biology subject of class X MIPA 1 can be seen from the teacher and student sides. The results of the observation of the teacher's ability to use the discovery learning model in the first class X MIPA 1 are still relatively low with a score of 39 or 81.25%, in the second cycle it has increased with a score of 46 or 95.83%, from an ideal score of 48. Students' cognitive abilities increased significantly until the achievement of learning objectives, with an average score of 92.64. The daily assessment score of students in cycle II in class X MIPA 1 totaled 28 students. There is a completeness of up to 100% of the 28 students, with the highest score of 100 and the lowest score of 89 which is above the KKM.